Manifestation of birds in the illumination of Javanese manuscripts - Ekowati, Venny Indria; Artanti, Yeni; Gedat, Remmy; Hartanto, Doni Dwi (Diksi, 2024)
Illuminations are decorative framing texts that are related to the content of the text. Illuminating Javanese manuscripts contain a variety of interesting symbols and ornaments that need to be revealed its meanings. One of the dominant ornaments in Javanese manuscript illumination is in the form of birds. The data of this study were 150 Javanese manuscripts with illumination from the collection of Sonobudoyo Museum and the Library of Balai Bahasa Yogyakarta. This research was built using qualitative methods with a hermeneutic approach to describe the manifestation of the bird symbol found in the illumination of Javanese texts. The hermeneutic approach is used in the analytical approach because the data used must be understood deeply through the symbols that appear in the illumination. The results of the present research show that: (1) the most common bird species used in illumination are eagles manifested as Garudha yeksa, sawat, and mirong, (2) the majority rationale (91%) of creating illumination of bird motifs is as the representation of the King, and (3) results of symbol interpretation establish a relationship between the symbol and the text. There were ornaments symbolising the King such as snakes, birds, crowns, batik motifs, leaves, houses, palaces, and others. Most ornaments contain meaning corroborating the contents of the manuscripts. For example, the change of power is symbolised by the cakra manggilingan, the HB (Hamengku Buwana) symbol shows the king on throne, and the bird symbolises and represents the king. The ornaments of birds in particular have the functions of didactic, aesthetic, and legitimacy.